The influence of leadership on employee performance with work discipline as an intervening variable PT. Supra Primtama Nusantara (Case Study of Duri Kepa Branch Employees) - Daspar; Suryadi (Jurnal Mantik, 2024)
The purpose of this study is to determine the Influence of Leadership Style on Employee Performance with Work Discipline as An Intervening Variable Of PT employees. Supra Primatama Nusantara (Biznet Network). This type of research uses quantitative methods. The sample of this study amounted to 30 respondents, the sample of this study was saturated. Data collection includes observation, questionnaire distribution and literature study. Validity tests, reliability tests, multicollinearity tests and hypothesis tests are used as analysis methods. Research using the SMART PLS program, Leadership Style Variable (X) has an influence on Employee Performance (Y) with a path coefficient (0.656) with a result of f square 1.551. Variable Leadership Style (X) has an influence on Work Discipline (Z) with a path coefficient (0.617) with a result of f square 0.616. Variable Work Discipline (Z) has an influence on Employee Performance (Y) with a path coefficient (0.345) with a result of f square 0.430. Indirect hypothesis testing on Leadership Style (X) on Employee Performance (Y) with Work Discipline (Z) as the Intervening Variable. has a path coefficient effect of 0.213 with the t-statistic value for this construct relationship is 1.900 which shows that the value of t-calculate. Which means that there is an indirect influence between Leadership Style (X) on Employee Performance (Y) and the variable Work Discipline (Z) is not proven